Single-Layer Raster CNN simulator using RK-Gill - Wahed, M. El Sayed; Kader, Wael M.; YosefÂ , Eyman (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
An efficient numerical integration algorithm for single layer Raster Cellular Neural Networks (CNN) simulator is presented in this paper. The simulator is capable of performing CNN simulations for any size of input image, thus a powerful tool for researchers investigating potential applications of CNN. This paper reports an efficient algorithm exploiting the latency properties of Cellular Neural Networks along with numerical integration techniques; simulation results and comparisons are also presented.